Mechanistic evaluation of the inhibitory effect of four SGLT-2 inhibitors on SGLT 1 and SGLT 2 using physiologically based pharmacokinetic (PBPK) modeling approaches - Zhang, Yu; Xie, Panpan; Li, Yamei; Chen, Zhixing; Shi, Aixin (Frontiers in Pharmacology, 2023)
Sodium-glucose co-transporter type 2 (SGLT2, gliflozins) inhibitors are potent orally active drugs approved for the management of type 2 diabetes. SGLT2 inhibitors exert a lowering-glucose effect through the suppression of sodium-glucose cotransporters 1 and 2 in the intestinal and kidney proximal tubules. In this study, we developed a physiologically based pharmacokinetic(PBPK) model and simulated the concentrations of ertugliflozin, empagliflozin, henagliflozin, and sotagliflozin in target tissues. We used the perfusion-limited model to illustrate the disposition of SGLT2 inhibitors in vivo. The modeling parameters were obtained from literatures. The simulation of gliflozin steady-state plasma concentration curves are similar to the observed steady-state plasma concentrations, the 90% prediction interval of simulated excretion of drugs in urine captured the observed data well, furthermore, the predicted pharmacokinetic parameters of gliflozins in humans were within two-fold errors of the observed values. At the approved doses, we estimated the effective concentrations in intestinal and kidney proximal tubules and calculated the inhibition ratio of SGLT receptors to differentiate the relative inhibition capacities of SGLT1 and 2 in each gliflozin. Simulation results showed that the approved dosages of ertugliflozin, empagliflozin, henagliflozin, and sotagliflozin can inhibit SGLT2 nearly completely. Sotagliflozin exhibited the highest SGLT1 inhibition ratio, followed by ertugliflozin, empagliflozin, and henagliflozin, all of which showed a lower SGLT1 inhibitory effect. The PBPK model successfully simulates the specific target tissue concentration that cannot be measured directly and clearly quantifies the relative contribution toward SGLT1 and 2 for each gliflozin.